Cognitive Function in Sickle Cell Disease Across Domains, Cerebral Infarct Status, and the Lifespan: A Meta-Analysis. (3rd May 2019) - Prussien, Kemar V; Jordan, Lori C; DeBaun, Michael R; Compas, Bruce E
Abstract: Objective: To provide a comprehensive quantitative review of neurocognitive function in sickle cell disease (SCD) across multiple domains, cerebral infarct status, and the lifespan. Methods: One hundred and ten studies were identified in PubMed, MedLine, and PsycINFO involving 110 studies of 3, 600 participants with SCD and 1, 127 sibling or health controls. Results: Meta-analytic findings indicate significant deficits across all neurocognitive domains, age groups, and infarct status. Significant deficits relative to the normative mean ranged from Hedges' g = −.39 to g = −.63 in preschool children, g = −.83 to g = −1.18 in school-aged children and adolescents, and g = −.46 to g = −.86 in adults. Deficits in full scale IQ (FSIQ), verbal reasoning, perceptual reasoning, and executive function increased from preschool to school-aged samples. However, findings also showed that deficits were smaller in adult samples relative to school-aged samples, likely due to sampling bias in adult studies. Findings across infarct status in sickle cell anemia showed that deficits ranged from g = −.54 to g = −.65 in samples without infarcts, g = −.52 to g = −1.03 in samples with silent cerebral infarct, and g = −1.35 to g = −1.82 in samples with stroke. Deficits in each domain increased in magnitude from no infarct or stroke, to silent cerebral infarct, to overt stroke. Conclusion: Individuals with SCD are at risk for cognitive deficits across domains, infarct status, and the lifespan. More research is necessary to determine unbiased effects for cognitive function in adults with SCD.